2021
DOI: 10.1111/cge.14054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, genetic, and histological features of centronuclear myopathy in the Netherlands

Abstract: Centronuclear myopathy (CNM) is a genetically heterogeneous congenital myopathy characterized by muscle weakness, atrophy, and variable degrees of cardiorespiratory involvement. The clinical severity is largely explained by genotype (DNM2, MTM1, RYR1, BIN1, TTN, and other rarer genetic backgrounds), specific mutation(s), and age of the patient. The histopathological hallmark of CNM is the presence of internal centralized nuclei on muscle biopsy. Information on the phenotypical spectrum, subtype prevalence, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…Overall, our cohort confirmed that disease onset occurs predominantly in infancy and early childhood, 4 , 10 although DNM2 -related CNM was initially identified in families showing late-onset CNM. 9 This may be in part due to the nature of patient-reported retrospective data, whereby patients report symptoms years before presenting to medical care.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Overall, our cohort confirmed that disease onset occurs predominantly in infancy and early childhood, 4 , 10 although DNM2 -related CNM was initially identified in families showing late-onset CNM. 9 This may be in part due to the nature of patient-reported retrospective data, whereby patients report symptoms years before presenting to medical care.…”
Section: Discussionsupporting
confidence: 73%
“…The most reported cases are boys with X-linked myotubular myopathy (XLMTM) due to mutations of MTM1 3 ; however, a recent study in the Netherlands found DNM2 to be a more common cause of CNM in their cohort. 4 Mutations of BIN1 , which is an autosomal recessive CNM, are relatively rare. 5 Mutations in TTN , RYR1 , and SPEG can also produce a congenital myopathy with internal nuclei.…”
mentioning
confidence: 99%
“…The moderate or scarce cognitive defects reported in CNM patients might be related to compensatory mechanisms that could operate in humans, despite the potential impact of the p.R465W mutation on hippocampal neuronal morphology and synaptic function that we observed in a mouse model of the disease. Notably, there is no clear genotype–phenotype correlation in the autosomal dominant CNM; however, patients exhibit marked interfamilial and intrafamilial variability [115–117], suggesting other factors besides mutations might influence the neurological phenotype in the CNM context. Therefore, the p.R465W mutation, and other autosomal dominant mutations in Dyn2, may or may not cause evident neurological defects.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there is no clear genotype-phenotype correlation in the autosomal dominant CNM; however, patients exhibit marked interfamilial and intrafamilial variability [115][116][117], suggesting other factors besides mutations might influence the neurological phenotype in the CNM context. Therefore, the p.R465W mutation, and other autosomal dominant mutations in Dyn2, may or may not cause evident neurological defects.…”
Section: Htz Defects In the Excitatory Synaptic Transmissionmentioning
confidence: 99%
“…1 AD-CNM results from heterozygous mutations in the DNM2 gene, which encodes dynamin 2 (DNM2), 2,3 and to date, 37 mutations (mainly missense) have been identified. 2,[4][5][6][7][8][9][10][11] Dominant DNM2 mutations also cause rare cases of Charcot-Marie-Tooth pe-ripheral neuropathy (CMT) (MIM: 606482) 12 and hereditary spastic paraplegia. 13 DNM2 belongs to the superfamily of large guanosine triphosphatases (GTPases) and is involved in endocytosis and intracellular vesicle trafficking through its role in deformation of biological membranes by oligomerization at the neck of membranes invagination, leading to the release of vesicles.…”
Section: Introductionmentioning
confidence: 99%